ANALISIS PROMOSI, HARGA DAN LABELISASI HALAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK WARDAH DI MASA PANDEMI COVID-19 (STUDI MASYARAKAT DESA BARENGKOK, DESA LEUWIMEKAR DAN DESA KAREHKEL, KECAMATAN LEUWILIANG, KABUPATEN BOGOR) - Dina, Putri Mey; Trihantana, Rully; Suryani, Ermi (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
During the Covid-19 Pandemic, various government policies greatly affected human life, one of which was restrictions on work activities, this was felt by Wardah's company with the policy shifting its sales to online platforms. The purpose of this study is to analyze and explain promotion variables, price variables and halal labeling variables that have an effect (positive/negative) or no effect (positive/negative) partially and simultaneously on purchasing decisions for wardah products during the Covid-19 pandemic. The research method used is a quantitative method, with data collection using a questionnaire sheet and google form with a Likert scale measurement. The sample of this study used Isaac and Michael's formula with a total sample of 342 people with non-probabilistic sampling and the method used was purposive sampling. The method of analysis used is multiple regression analysis using SPSS Version 23 and Microsoft Excel. The results of this study are (a) Halal Promotion, Price and Labeling have a partial positive effect on Wardah Product Purchase Decisions during the Covid-19 pandemic (b) Halal Promotion, Price and Labeling have a simultaneous positive effect on Wardah Product Purchase Decisions during the Covid pandemic -19.